The relationship between husband support and husband's education level with fertility of women of childbearing age in East Nusa Tenggara Province, Indonesia - Ari Asri Dayanti; Siti Nurrochmah; Lucky Radita Alma (AOSIS, 2022)
Fertility is a contributor to the number of figures in the increase in population. The husband has a big role in the fertility process of his wife. The purpose of this study was to examine the relationship between the incidence of women of childbearing age fertility with husband support and the level of husband education in NTT Province. The design used in this study was cross-sectional. The data used is secondary data, which is sourced from the documentation of 2017 Indonesian Demographic and Health Survey (IDHS). The population of this study was all women of childbearing age in NTT Province in 2017, namely 2,223 women, and the sample used in this study was 323 women. Data analysis was carried out univariate and bivariate, using the Chi-Square Test. The results of the bivariate analysis were that there was no significant relationship between husband support and women of childbearing age fertility (pvalue= 0.219), and there was a significant relationship between the husband's education level and women of childbearing age fertility (p-value=0.006).